Power absorption inside helicon plasma of helium RF ion source in nonaxial magnetic field - Alexenko, O.V.; Miroshnichenko, V.I.; Voznyi, V.I. (Вопросы атомной науки и техники, 2015)
The paper studies integral and one-dimensional distribution of RF electromagnetic field absorption in a helicon plasma with external magnetic field directed at an angle to a plasma plane. A simplified model of a helicon plasma plane layer is used here. Calculation results are used to explain power absorption in a compact helicon ion source with nonuniform external magnetic field. An ion source is a part of a nuclear scanning microprobe (NSMP) injector at the Institute of Applied Physics NAS of Ukraine. Calculations for ion source parameters of the NSMP injector show a resonant behaviour of integral RF power absorption as a function of a magnetic field inclination angle. A model (planar) geometry is verified here for solution of this problem. Досліджуються інтегральний та одномірний розподіли поглинання ВЧ-електромагнітного поля в геліконній плазмі із зовнішнім магнітним полем, яке має напрямок під кутом до поверхні плазми. Використано спрощену модель плоского шару геліконної плазми. Результати розрахунків застосовуються для пояснення поглинання потужності в компактному геліконному джерелі іонів з неоднорідним зовнішнім магнітним полем. Джерело іонів входить до складу інжектора ядерного скануючого мікрозонда (ЯСМЗ) Інституту прикладної фізики НАН України. Розрахунки для параметрів джерела іонів інжектора ЯСМЗ демонструють резонансний характер інтегрального поглинання ВЧ-потужності в залежності від кута нахилу магнітного поля. Виконано перевірку правомірності застосування модельної (плоскої) геометрії для вирішення задачі. Исследуются интегральное и одномерное распределения поглощения ВЧ-электромагнитного поля в геликонной плазме с внешним магнитным полем, которое направлено под углом к поверхности плазмы. Используется упрощенная модель плоского слоя геликонной плазмы. Результаты расчетов применяются для объяснения поглощения мощности в компактном геликонном источнике ионов с неоднородным внешним магнитным полем. Источник ионов входит в состав инжектора ядерного сканирующего микрозонда (ЯСМЗ) Иститута прикладной физики НАН Украины. Расчеты для параметров источника ионов инжектора ЯСМЗ показывают резонансный характер интегрального поглощения ВЧ-мощности в зависимости от угла наклона магнитного поля. Выполнена проверка правомерности применения модельной (плоской) геометрии для решения задачи.